Exploration of piperazine-derived thioureas as antibacterial and anti-inflammatory agents. In vitro evaluation against clinical isolates of colistin-resistant Acinetobacter baumannii. Issue 18 (15th September 2020) - Mazzotta, Sarah; Cebrero-Cangueiro, Tania; Frattaruolo, Luca; Vega-Holm, Margarita; Carretero-Ledesma, Marta; Sánchez-Céspedes, Javier; Cappello, Anna Rita; Aiello, Francesca; Pachón, Jerónimo; Vega-Pérez, José Manuel; Iglesias-Guerra, Fernando; Pachón-Ibáñez, María Eugenia
Graphical abstract: Highlights: A set of 39 piperazine-derived thioureas was evaluated against colistin-resistant Acinetobacter baumannii clinical strains. Six derivatives inhibited bacterial growth of 46% of the A. baumannii strains at low micromolar concentrations. Bactericidal activity (time kill curve) was tested for compound 41 against two colistin-resistant A. baumannii strains. Compound 41 was also tested for synergistic combination with colistin against the same two clinical strains. Their potential anti-inflammatory activity was assessed by their ability to inhibit the production of nitric oxide. Abstract: A. baumannii is one of the most important multidrug-resistant microorganisms in hospital units. It is resistant to many classes of antibiotics and the development of new therapeutic strategies is necessary. The aim of this study was to evaluate the antibacterial activity of a set of piperazine-derived thioureas against 13 clinical strains of colistin-resistant A. baumannii . Six derivatives were identified to inhibit bacterial growth of 46% of the A. baumannii strains at low micromolar concentrations (Minimum Inhibitory Concentration from 1.56 to 6.25 μM). A common structural feature in most active compounds was the presence of a 3, 5-bis-trifluoromethyl phenyl ring at the thiourea function. In addition, the ability of the compounds to inhibit production of nitric oxide (NO) was examined in RAW 264.7 murine macrophages, highlighting the potential of piperazine-derived thioureas as promising scaffolds for the design of new combined anti-bacterial/anti-inflammatory agents.